2005
DOI: 10.1016/j.pain.2005.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Differences in brain responses to visceral pain between patients with irritable bowel syndrome and ulcerative colitis

Abstract: Patients with mild chronic inflammation of the rectum or ileum have reduced perceptual responses to rectosigmoid distension compared to patients with irritable bowel syndrome (IBS). The current study sought to identify differences in regional cerebral blood flow (rCBF) during rectal distension, which might correspond to these perceptual differences. In 8 male ulcerative colitis (UC) patients with quiescent disease, 7 male IBS patients and 7 healthy male controls, rCBF was assessed using 15O-water positron emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 257 publications
(207 citation statements)
references
References 68 publications
11
194
1
1
Order By: Relevance
“…To date, the majority of human studies in this field have used distension of the rectosigmoid colon [4,5,8,41,44,48,52,62], stomach [37,69], and esophagus [2,3,9,73]. Activation of the insular and dorsal anterior cingulate cortex (dACC) has been most consistently reported, with other brain regions, including the prefrontal cortex, thalamus and brainstem being reported in some, but not in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of human studies in this field have used distension of the rectosigmoid colon [4,5,8,41,44,48,52,62], stomach [37,69], and esophagus [2,3,9,73]. Activation of the insular and dorsal anterior cingulate cortex (dACC) has been most consistently reported, with other brain regions, including the prefrontal cortex, thalamus and brainstem being reported in some, but not in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…28 The altered responses in the emotional-arousal network during visceral stimulation were shown in IBS patients by means of brain imaging techniques. [37][38][39] These brain regions are closely related to stress responses which often induce cardiovascular activation. However, meal stimulation may not directly affect the brain regions which mediate pathophysiological conditions of IBS.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are abnormal in patients suffering from IBS and about 35% of the IBS patients have chronic pelvic pain. 67 Mayer et al 68 reported that IBS patients exhibit increased activation of brain regions that are linked to perception of rectal distension and Mertz et al 69 showed differences in brain activation patterns in response to a painful rectal stimulus in IBS patients compared to controls. Many studies have also shown that those with IBS have amplified visceral sensitivity in response to stress 70 or food intake.…”
Section: Alterations Of the M Icrobiome In Visceral Pain Disordersmentioning
confidence: 99%